Is the Institutional Budget Effective to Enhance The Work Achievement of Certified Teachers? – Mediating Role of Work Commitment - Prasetyo, Gaguk Tri; Ariwibowo, Agung; Budiyanto; Hariyati, Nunuk; Panjaitan, David (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2024)
Certified educators play an important role in improving the quality of education because certification shows that a teacher has adequate competence, both in knowledge and teaching skills. Therefore, a budget policy that supports certified teachers is crucial, including a good take home pay and incentive mechanism, so as to support the achievement of teachers' basic needs and improve their work performance. This study then aimed to explore the role of take-home pay and incentives on teacher work performance through their commitment. This study was conducted with a quantitative approach, with the selected sample being Elementary School and Junior High School Teachers in Mojokerto City, Indonesia. The research data were analyzed using path analysis with the help of the SPSS program. From data analysis, it was showed that the relationships between Take Home Pay, Incentives, and Work Commitment towards Teacher Work Achievement, as well as between Take Home Pay and Incentives towards Teacher Work Commitment, all show t-statistics that are well above the critical t-values of 1.98 at the 5% significance level and 2.63 at the 1% significance level. This suggests that both financial incentives (Take Home Pay and Incentives) and non-financial factors (Work Commitment) are important drivers of teacher performance and commitment of certified teacher in Mojokerto City. Overall, these findings reinforce the importance of supporting teachers with both financial and non-financial incentives to enhance their work achievement and commitment.